Hydrogen evolution activity tuning via two-dimensional electron accumulation at buried interfaces. Issue 36 (27th August 2019) - Xue, Yudong; Fishman, Zachary S.; Wang, Yunting; Pan, Zhenhua; Shen, Xin; Yanagi, Rito; Hutchings, Gregory S.; Liu, Mingzhao; Zheng, Shili; Zhang, Yi; Altman, Eric I.; Hu, Shu
Abstract : The buried electrocatalytic interfaces between bimetallic sulfide nanosheets and ALD TiO2 coatings achieved remarkable HER activity improvement, offering a general strategy for improving the charge-transfer kinetics of an electrocatalytic system. Abstract : Developing efficient earth-abundant transition metal-based electrocatalysts for the hydrogen evolution reaction (HER) is crucial for hydrogen production at scale. This paper reports that the buried electrocatalytic interfaces between Ni–Fe sulfide (NiFeS) nanosheets and TiO2 conformal coatings (about 5 nm) achieved remarkable HER activity improvement, lowering the HER overpotential from −170 mV to −107 mV at −50 mA cm −2 in a base. Non-HER active, permeable TiO2 coatings grown by atomic layer deposition (ALD) achieved continuous fine-tuning of the electronic properties at the buried TiO2 /NiFeS interfaces, as a novel strategy and the main factor for electron accumulation at the interface. Core-level and valence band X-ray photoelectron spectroscopy (XPS) was used to investigate the TiO2 electronic-structure tuning effect on the charge-transfer energetics during the HER. Their alkaline HER mechanism was elucidated by supplementing characterizations of membrane permeation, Tafel slope, and synchrotron X-ray absorption spectroscopy, which verified that the buried TiO2 /NiFeS interfaces are electrocatalytically active. This study offers a general strategy for improving the charge-transfer kinetics of an electrocatalytic system by confining catalysis at a permeable solid–solid interface. The broad applicability of permeable and tunable coatings potentially accelerates the optimization of earth-abundant catalysts to achieve high performance under operationally relevant conditions.